Microbial use of recycled urea is dependent on the level and frequency of degradable intake protein supplementation - Wickersham, T.A.; Cochran, R.C.; Wickersham, E.E.; Moore, E.S.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Protein supplementation increases utilization (intake and digestion) of low-quality forage and ultimately animal performance. Despite its effectiveness, protein supplementation is often expensive. One strategy to reduce the cost of supplementation is to supplement less frequently than daily, generally every other day or every third day. By reducing the frequency of supplementation, the cost of delivering the supplement is reduced. Reducing the frequency of supplementation is an effective strategy for reducing cost, and it only minimally impacts animal performance, with less frequent supplementation resulting in slightly greater losses of body condition score and body weight during the winter supplementation period. Urea recycling, the transfer of urea from the animal’s body to the gastrointestinal tract, has been suggested as a mechanism that allows infrequently supplemented cattle to perform similarly to cattle supplemented daily. However, little data is available to substantiate this claim, and such data would be useful in helping nutritionists better understand nitrogen metabolism in infrequently supplemented ruminants. Our objective was determine the role of urea recycling in meeting ruminal nitrogen requirements in infrequently supplemented cattle fed low-quality forage.
Keywords: Beef; Cattle; Protein supplementation; Urea